Oxidative DNA damage and subclinical hypothyroidism in children with obesity - Inass Hassan Ahmad; Marwa khairy Abd Elwahab; Mervat El Shahat El Wakeel; Mohamed A. M. Kamal; Marwa Elhady (SpringerOpen, 2021)
Abstract Background Obesity-related oxidation stress plays a key role in obesity complications; however, its relation to thyroid status is an area for further research. The study aimed to assess thyroid function in obese children and its relation to oxidative deoxyribonucleic acid (DNA) damage. Results Fifty obese and 40 normal weight children were included. Anthropometric measurement, lipid profile, thyroid function, anti-thyroglobulin antibody, thyroid peroxidase antibody, and 8-hydroxydeoxyguanosine serum level as marker of oxidative DNA damage were measured. Thirty-six percent of children with obesity have subclinical hypothyroidism. Central obesity but not oxidative DNA damage and lipid profile was significantly associated with subclinical hypothyroidism. Waist circumference > 97th centile increases the risk for subclinical hypothyroidism (odd ratio 10.82; confidence interval 95% 2.75-42.409; p-value<0.001). Conclusion Central obesity represents a risk factor for subclinical hypothyroidism in obese children. Oxidation DNA damage did not show significant association with subclinical hypothyroidism.